A fly-wing smoke screen to improve the smoke exhaustion performance of a vertical shaft in road tunnel. (July 2021) - Zhang, Shaogang; Huang, Yilong; Shi, Long; Lin, Bin; Li, Xianbin; Wu, Yujian; Wang, Jinhui
Highlights: Fly-wing smoke screen is used to improve smoke exhaustion of vertical shaft. Plug-holing is prevented effectively by fly-wing smoke screen. Smoke exhaustion is improved evidently under the help of fly-wing smoke screen. A range of included angle is obtained for the better smoke exhaustion performance. Mechanism of fly-wing smoke screen in improving smoke exhaustion is discussed. Abstract: A series of numerical simulations were carried out to investigate the effectiveness of a fly-wing smoke screen in improving smoke exhaustion performance in a naturally ventilated urban road tunnel with vertical shafts. The fly-wing smoke screens with different included angles ( 0 ° < θ ≤ 180 ° ) were installed under the tunnel ceiling. The numerical results showed that plug-holing was prevented effectively by the fly-wing smoke screen, which stops, gathers, and then guides the smoke to the shaft vent. The velocity field under the tunnel ceiling showed that the optimal included angle with better smoke exhaustion performance was 60 ° ≤ θ ≤ 120 ° . The curve of CO mass flow rate through vertical shaft can be divided into three regions. The best included angle of fly-wing smoke screen is found at 90° with the best smoke exhaustion efficiency. An empirical formula is proposed to describe the exhaustion improvement effectiveness of fly-wing screen. The variation of smoke exhaustion improvement is mainly dominated by the coupling effect of smoke gathering and flow-guidance of the fly-wing smoke screen under different included angles. The practical engineering application of the proposed fly-wing smoke screen in urban tunnels with vertical shaft is also presented. This research offers a basic reference for the design of those naturally ventilated road tunnels with vertical shaft and fly-wing smoke screen.